Longitudinal OCTA vessel density loss in macula and optic nerve head in healthy, glaucoma suspect and established glaucoma eyes - Wu, Jo-Hsuan; Moghimi, Sasan; Nishida, Takashi; Adelpour, Mohsen; Kamalipour, Alireza; Gunasegaran, Gopikasree; Zangwill, Linda M; Weinreb, Robert N (British journal of ophthalmology, 2025)
To examine longitudinal optical coherence tomography angiography (OCTA) changes in macula and optic nerve head (ONH) in healthy, glaucoma suspect (GS) and primary open-angle glaucoma (POAG) eyes. Healthy, GS and POAG eyes from Diagnostic Innovations in Glaucoma Study with ≥2 years follow-up and four visits of macular/ONH OCTA imaging were included. Rates of macular wiVD (whole-image vessel density) and ONH wiCD (whole-image capillary density) changes were calculated for each diagnosis group using join mixed-effect modelling. Differences in wiVD/wiCD change rates across diagnoses were examined through pairwise comparison. Relationships of baseline 24-2 visual field (VF) mean deviation (MD) with wiVD/wiCD change rates were evaluated for POAG eyes. There were 36, 57 and 79 eyes (25, 38 and 50 subjects) in healthy, GS and POAG groups, respectively. Rates of wiVD (range:-0.72 to -0.92 %/year) and wiCD (range:-0.28 to -0.66 %/year) loss were different from zero in all groups (p<0.05). The rates of wiCD loss differed across all diagnosis groups (p<0.001), while wiVD change rates did not increase when comparing healthy to GS eyes (p=0.167). Baseline VF MD showed a significant but modest correlation with the rates of both wiVD and wiCD loss (p<0.05), and the correlation with wiCD change rate was slightly stronger (R =0.27 vs 0.16). In glaucoma, there is earlier microvasculature loss in the ONH than in the macula. Moreover, ONH VD loss shows a slightly stronger association with baseline VF than macular VD. Observing ONH VD loss with OCTA may help to monitor early glaucoma, which should be confirmed by future larger studies.